Chronic Fatigue Syndrome and Cardiovascular Disease: JACC State-of-the-Art Review - Natelson, Benjamin H; Brunjes, Danielle L; Mancini, Donna (Journal of the American College of Cardiology, 2021)
Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a medically unexplained illness characterized by severe fatigue limiting normal daily activities for at least 6 months accompanied by problems with unrefreshing sleep, exacerbation of symptoms following physical or mental efforts (postexertional malaise [PEM]), and either cognitive reports or physiological evidence of orthostatic intolerance in the form of either orthostatic tachycardia and/or hypocapnia. Although rarely considered to have cardiac dysfunction, ME/CFS patients frequently have reduced stroke volume with a significant inverse relation between cardiac output and PEM severity. Magnetic resonance imaging of ME/CFS patients compared with normal control subjects found significantly reduced stroke, end-systolic, and end-diastolic volumes together with reduced end-diastolic wall mass. Another cardiovascular abnormality is reduced nocturnal blood pressure assessed by 24-hour monitoring. Autonomic dysfunction is also frequently observed with postural orthostatic tachycardia and/or hypocapnia. Two consecutive cardiopulmonary stress tests may provide metabolic data substantiating PEM.